2021
DOI: 10.1042/cs20210602
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota transplants from feces or gut content attenuated portal hypertension and portosystemic collaterals in cirrhotic rats

Abstract: Liver cirrhosis and portal hypertension is the end of chronic liver injury with hepatic, splanchnic and portosystemic collateral systems dysregulation. Liver injury is accompanied by gut dysbiosis whereas dysbiosis induces liver fibrosis, splanchnic angiogenesis and dysregulated vascular tones vice versa, making portal hypertension aggravated. It has been proved that intestinal microbiota transplantation alleviates dysbiosis. Nevertheless, the influences of microbiota transplantation on cirrhosis related porta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The situation in which fibrotic bands and regeneration nodules compress the hepatic vasculature may cause abnormal vessel structures, while irregular vasoconstriction hinders blood flow. 40,41 Based on the significantly enhanced AST and total bilirubin expressions in plasma (Fig. 2b and 2c), we speculated that the increased hepatic vascular resistance in the ALPND-treated group was attributed to enhanced liver injury of the setting.…”
Section: Resultsmentioning
confidence: 98%
“…The situation in which fibrotic bands and regeneration nodules compress the hepatic vasculature may cause abnormal vessel structures, while irregular vasoconstriction hinders blood flow. 40,41 Based on the significantly enhanced AST and total bilirubin expressions in plasma (Fig. 2b and 2c), we speculated that the increased hepatic vascular resistance in the ALPND-treated group was attributed to enhanced liver injury of the setting.…”
Section: Resultsmentioning
confidence: 98%
“…Based on this, Sun et al [ 24 ] reported a case of HM in a patient who received FMT, and neurological function improved after three repetitions of FMT. More studies have revealed that repairing gut microbiota may decrease portal hypertension and repair the blood-brain barrier[ 25 , 26 ]. Further, there is increasing data to demonstrate the usefulness of FMT for improving HE[ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“… Traykova et al (2017) reported that when bacterial translocation occurred, the number of bacterial species and the total bacterial DNA were positively correlated with the serum nitric oxide level [odds ratio (OR): 0.64, 95% confidence interval (CI): 0.247–0.852, P = 0.0041 and OR: 0.62, 95% CI: 0.216–0.842, P = 0.0062, respectively] and were inversely correlated with systemic vascular resistance (OR: −0.593, 95% CI: −0.83 to −0.175, P = 0.0095 and OR: −0.621, 95% CI: −0.843 to −0.218, P = 0.0060, respectively). Huang et al (2021) also found that fecal microbiota transplantation (FMT) restored the normal gut microbiota composition and downregulated phosphorylated endothelial nitric oxide synthase, leading to improved vasodilation. Therefore, we speculated that the gut microbiota in sepsis patients may promote increased renal blood flow by participating in the SIRS response, leading to ARC.…”
Section: Gut–kidney Crosstalk In Sepsismentioning
confidence: 98%
“…However, relevant research has not directly reached this conclusion. Although studies have shown that the gut microbiota affected nitric oxide expression, these reports experimented with cirrhosis, and it is unclear whether the underlying disease affected this process ( Traykova et al, 2017 ; Huang et al, 2021 ).…”
Section: Gut–kidney Crosstalk In Sepsismentioning
confidence: 99%